Preparation and Properties of a ZnO/PVA/β‐CD Composite Electrode for Rechargeable Zinc Anodes. Issue 38 (16th October 2018) - Zhang, Zejie; Zhou, Debi; Li, Zhihui; Zhou, Liang; Huang, Boyun
Abstract: ZnO/PVA/β‐CD composite electrode was prepared by chemical crosslinking method. The FT‐IR spectrum of the composite electrode shows that the absorption peaks in 3379 cm −1 owing to the O−H stretching vibration decreased significantly, indicating the decreased of the hydroxyl number. The blue shift of the absorption peak at 3900 cm −1 owing to the O−H stretching vibration proves that the complex substance formed after cross‐linked reaction is more stable. Compared with the bare electrode, the cycle numbers of the composite electrode increased from 40 to 80 before the discharge capacity of the battery reduced to 80% of the maximum capacity at the charge/discharge current density of 25 mA⋅cm −2, which revealed that the cycle life of the composite electrode was longer than the bare electrode. SEM spectrum of the composite after 80 cycles that the active substances were embedded in the composite electrode regularly with good morphology and no obvious dendrite while there was a large number of dendrite inside the bare electrode, which indicated that there was an effect of combination between the complex substance and the active Zn. The results of the polarization curves and the AC impedance measurements show that the composite electrode has high electrochemical activity and low internal resistance. Abstract : Some regular pores were presented in the internal of the ZnO/PVA/β‐CD electrode after 80 cycles. These three‐dimensional channels could be due to the hydrophobic inner cavity in β‐CD and complexation with Zn ions, making PVA/β‐CD complexes with ZnO particles together and uniform distribution within the electrode. The porous three‐dimensional structure of the electrode is beneficial to the migration of ions in the electrolyte, improving the conductivity of the electrode and the stability of circulation.